EFFECT OF POSITIONING ON PURCHASING DECISIONS ON SOSRO BOTTLE TEA PRODUCTS (Survey / Census on UNSIKA Students) - Devi Ratnasari; Diah Febi Utami; Dikka Ramadhan R; Edi Sukendar; Fanny Tania; Reminta Lumban Batu (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2019)
The purpose of the study was to find out the description of Positioning, to find out the description of the Purchase Decision, to find out how much influence Positioning had on the Purchase Decision. The population in this study were students of the University of Singaperbangsa Karawang who had consumed Teh Botol Sosro as many as 16,291 and taken as many as 100 respondents using the Slovin formula with an error rate of 10% through random sampling method. The analysis technique used is simple linear regression analysis and classic assumption test. Tests were carried out with the help of SPSS version 24 software. The results of the study showed that the positioning partially had a positive and significant effect on purchasing decisions. This conclusion shows that positioning has a good influence so that it encourages consumers to make purchasing decisions on a product, especially Teh Botol Sosro products. Therefore, this research is expected to be carried out widely by future researchers.